2023
DOI: 10.37502/ijsmr.2023.6102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Income Inequality on the Economic Growth of Nigeria

Abstract: This study investigated the effect of income inequality on the economic growth in Nigeria from 1981-2021, Ordinary least squared (OLS) method of data analysis was adopted because of its Best Linear Unbiased Estimators (BLUE) properties. The variables used were sourced from Central Bank of Nigeria Statistical Bulletin. The variables used were income inequality, employment, education, poverty and government capital expenditure and real gross domestic product. The collected data were sourced from central bank of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 1 publication
1
9
1
Order By: Relevance
“…Barro (2013) has similar finding in their study that domestic investment encourages economic growth. Money supply is found strong significant and positive effect on growth which supports the theoretical argument that money supply promotes economic growth (Ershad and Mahfuzul, 2017;Chude and Chude, 2016). The elasticity of the money supply is 0.11, which refers that a 1% raise in money supply leads to a 0.11% raise in economic growth.…”
Section: Hausman Specification Testsupporting
confidence: 74%
“…Barro (2013) has similar finding in their study that domestic investment encourages economic growth. Money supply is found strong significant and positive effect on growth which supports the theoretical argument that money supply promotes economic growth (Ershad and Mahfuzul, 2017;Chude and Chude, 2016). The elasticity of the money supply is 0.11, which refers that a 1% raise in money supply leads to a 0.11% raise in economic growth.…”
Section: Hausman Specification Testsupporting
confidence: 74%
“…The finding also agrees with the results of Yoke and Chan (2018), who affirmed that when the CIT burden increases, the level of financial performance decreases. However, this finding contradicts the study of Chude and Chude (2015), Taiwo and Oyedekun (2022)…”
Section: Hypothesis Testingcontrasting
confidence: 68%
“…For example, found a positive association between CIT and the ROA of listed companies in Kenya. Chude and Chude (2015) Nigerian companies in the aspect of return on assets spanning 2000 to 2012. Earnings per share were used to measure profitability, while CIT was used as the independent variable to represent company tax.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…A current account deficit can either decrease or increase inflationary pressure depending on its impact on import and export prices, as well as domestic demand for imported goods and services (Alawin & Oqaily, 2017) [1] . Likewise, Chude and Chude (2015) [4] have found that foreign aid and market access can contribute on economic growth, but they also deteriorate the regulation of currency supply and domestic inflation. There are various factors that can affect the current account, including trade and current transfers such as foreign aid and workers' remittances, and these can impact inflation and current account in following ways (Alawin & Oqaily, 2017) [1] : Imports can have a dual impact on inflation in the domestic economy.…”
Section: Literature Reviewmentioning
confidence: 99%